A study of the immune response in murine experimental malaria, with special reference to the effects of South African medicinal plants, artesunate and chloroquine - Gumede, Bonginkosi (Division of Clinical Pharmacology, 2025)
The role of pro-inflarrnnatory cytokines (TNF and IFN-y) in a murine experimental malaria model for cerebral malaria is reported in this thesis. Wild type and receptor knockout mice (IFN-y deficient mice (IFN-l") and TNF-a/fr1- double deficient) were infected with Plasmodium berghei ANKA {PbA). PbA induced fatal cerebral malaria in wild type mice, which died within 5 to 8 days. In contrast, IFN-f1- and TNF-a/[r1-were completely resistant to PbA-induced cerebral malaria. Both wild type and mutant mice developed a similar degree of parasitaemia in the initial phase, and anaemia and leukocytosis were not different, showing that both anaemia and mobilisation of leukocytes occur in the absence of TNF and IFN-y. The results show that TNF'- and IFN,f'- mice are resistant to PbA-induced cerebral malaria, and confirm the role played by Thl cytokines in its pathogenesis. Plasmodium chabaudi chabaudi AS infection results in splenomegaly, and activation of the immune system. Resistant C57BL/6 mice, which eliminate the parasites and survive the infection, developed marked splenomegaly. Susceptible A/J mice develop minimal splenomegaly. In this work it has been shown that there is a rapid deterioration in splenic architecture, although immunohistochemistry confirmed preservation of a high level of structure and organisation. CD 11 c {dendritic) cells moved from the marginal zone into the CD4+ T cell area (where their antigen presenting function would be maximal). The juxtaposition of CDllc and T cells might be associated with immune complex formation in the spleen during the infection. The findings were similar for C57BL/6 and A/J mice. A 14-day course of artesunate 100 mg/kg prevented completely the development of parasitaemia and cerebral malaria in Plasmodium berghei ANKA infected mice, with survival of more than 60d. Chloroquine enhanced production of IL-10. Artesunate displayed enhanced IL-1 0 activity but no effect on production of pro-inflammatory cytokines. Extracts of W. salutaris, a South African medicinal plant, reduced parasitaemia by >50% at doses of 100 and 500mg/kg, and of A. annua reduced parasitaemia by 64% at a dose of 200 mg/kg. These extracts, and extracts of H. procumbens, had immunomodulatory activity on TNF-a., IFN-y, IL-12 and IL-10 production by Con A- and LPS-induced splenocytes.